THE EXPERIENCE OF THE COMPLEX ASSESSMENT OF THE IMPACT OF THE LENGTH OF AGRICULTURAL USE ON PROPERTIES AND REGIMES OF AGROCHERNOZEMS OF STONY STEPPE - I. I. Lebedeva; G. S. Bazykina; A. M. Grebennikov; Yu. I. Cheverdin; V. A. Bespalov (Бюллетень Почвенного института им. В.В. Докучаева, 2016)
The comparative study of impact of long term agricultural use (for 20, 60, and 120 years) on migratory-micellar (typical) chernozems of Stony Steppe (Voronezh oblast, Russia), was conducted. The following properties were investigated: morphology, humus state, structure, water and physical properties, and water and temperature regimes. It is revealed that agro-layers of chernozems are sustainable in time. Their residual specificities are preserved even under long-term (130 years) layland. During the first 10-20 years of agricultural use the decrease of humus content is revealed: the decrease of the humus content including the labile humus matter, and also the decrease of organic carbon content. Hereafter, there occurs the stabilization of their humus state, though on the lower layer, due to relative equilibrium with the processes of organic matter new formation. In the first years of the agricultural use there is observed the insignificant increase of the bulk density, deterioration of the structure and the decrease of the porosity, water capacity and plant available water content. Further the physical state of these layers of chernozems is preserved on the optimal level. The heath provision of the plowland is higher than that under the natural vegetation due to the heating to the higher temperatures which causes the physical desiccation and accumulation of carbonates in the surface layers. The water regime of chernozems as mixed-aged plowlands, and long-termed layland of Stony Steppe may be determined as periodically percolative regime with additional ground moistening. The main reason of that may be the presence of water-accumulating layer (200-300 cm) above the aquiclude, which is composed of clays lying at the depth of 300 cm.